Synthesis of novel unsymmetrical phthalocyanines substituted with crown ether and nitro groups - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
This work reports on the synthesis of new unsymmetrically substituted phthalocyanines (M = Zn, Cu, Co, Ni) bearing three benzo-15-crown-5 units through oxy bridges and a nitro group. Phthalocyanines were prepared by a statistical condensation of 4-nitro phthalonitrile and 1-{[(benzo-15-crown-5)-4'-yl]oxy}phthalonitrile in the presence of anhydrous metal salts. All the target unsymmetrical phthalocyanines were separated by column chromatography and characterized elemental analyses, H-1 NMR, IR, mass and UV-Vis spectral data. Electrochemical behaviors of Cu (II) phthalocyanine by cyclic voltammetry and differential pulse voltammetry techniques gave two common phthalocyanine ring reductions and one ring oxidation processes. Peak-to-peak separation of the processes II and III (388 mV) and the measure of gap (1.672 V) between the HOMO and LUMO for the complex, fits a phthalocyanine with electrochemically inactive metal center. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: unsymmetrical; metallophthalocyanines; synthesis; cyclic voltammetry; COPPER PHTHALOCYANINE; ELECTROCHEMICAL CHARACTERIZATION; ALKYLTHIO GROUPS; BRANCHED BULKY; COMPLEXES; METALLOPHTHALOCYANINES; TRIAZOLEPHTHALOCYANINES; MACROCYCLES; PORPHYRINS; DERIVATIVES